Cloning, soluble expression, and purification of the RNA polymerase II subunit RPB5 from Saccharomyces cerevisiae - Chhetri, Gaurav (Bioengineered, 2015)
We report the molecular cloning, expression, and single-step homogeneous purification of RNA polymerase II subunit RPB5 from Saccharomyces cerevisiae. RPB5 is a 210 amino acid nuclear protein that functions as the fifth largest subunit of polymerase II and plays a central role in transcription. The gene that codes for RPB5 was generated by amplification by polymerase chain reaction. It was then inserted in the expression vector pET28a(+) under the transcriptional control of the bacteriophage T7 promoter and lac operator. BL21(DE3) Escherichia coli strain transformed with the rpb5 expression vector pET28a(+)-rpb5 accumulates large amounts of a soluble protein of about 30 kDa (25 kDa plus 5 kDa double His(6)-Tag at N and C-terminal). The protein was purified to homogeneity using immobilized metal affinity chromatography. RPB5 recombinant protein was further confirmed by immunoblotting with anti-His antibody. In this study, the expression and purification procedures have provided a simple and efficient method to obtain pure RPB5 in large quantities. This will provide an opportunity to study the role of S. cerevisiae RPB5 in gene expression and transcription regulation. Furthermore, it can provide additional knowledge of the interaction partners of RPB5 during various steps of transcription and gene expression.